2014
DOI: 10.1002/pi.4834
|View full text |Cite
|
Sign up to set email alerts
|

Fibro‐porous poliglecaprone/polycaprolactone conduits: synergistic effect of composition and in vitro degradation on mechanical properties

Abstract: Blends of poliglecaprone (PGC) and polycaprolactone (PCL) of varying compositions were electrospun into tubular conduits and their mechanical, morphological, thermal and in vitro degradation properties were evaluated under simulated physiological conditions. Generally, mechanical strength, modulus and hydrophilic nature were enhanced by the addition of PGC to PCL. An in vitro degradation study in phosphate-buffered saline (pH 7.3) was carried out for up to 1 month to understand the hydrolytic degradation effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 48 publications
2
15
0
Order By: Relevance
“…Electrospun tubular scaffolds were fabricated by initially spinning a sacrificial layer of poly(vinyl alcohol) (PVA) onto a collector (a grounded cylindrical mandrel of 4 mm diameter rotating at 400 rpm) from a 10% (w/v) solution of PVA in water at a rate of 1 mL/h and an electric field strength of 1.5 kV/cm. The needle was driven along the length of the mandrel at a rate of 30 mm/s to guarantee that the polymer fibers would be deposited evenly [5]. After coating the mandrel with a thin layer of PVA, 2.5 mL of the PCL/PGC solution was spun onto it using the procedure described above.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Electrospun tubular scaffolds were fabricated by initially spinning a sacrificial layer of poly(vinyl alcohol) (PVA) onto a collector (a grounded cylindrical mandrel of 4 mm diameter rotating at 400 rpm) from a 10% (w/v) solution of PVA in water at a rate of 1 mL/h and an electric field strength of 1.5 kV/cm. The needle was driven along the length of the mandrel at a rate of 30 mm/s to guarantee that the polymer fibers would be deposited evenly [5]. After coating the mandrel with a thin layer of PVA, 2.5 mL of the PCL/PGC solution was spun onto it using the procedure described above.…”
Section: Methodsmentioning
confidence: 99%
“…Scaffolds for vascular tissue engineering must have the bioactivity necessary for cell adhesion/growth and mechanical properties matching those of native blood vessels to withstand the pressure exerted due to blood flow. To this end, electrospun tubular scaffolds were fabricated from biocompatible PCL and fast-degrading PGC blends [5, 6] and coated with a physiological protein matrix, HuBiogel™. In a recently published paper we have shown that the PGC/PCL composition affected both the degradation and mechanical properties of tubular scaffolds such that a 3:1 PCL/PGC blend exhibited miscibility and co-continuous phase with optimized mechanical properties for vascular graft [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a copolymer consist of randomly segmented polyglycolic acid PGA and polycaprolactone PCL. It has better degradation time shorter and mechanical properties in comparison with PCL Bezwada et al () and Patela et al ().…”
Section: Introductionmentioning
confidence: 98%
“…PGC consist of hard segment that gives the sutures its strength Bernstein et al (). PCL segment increased viscoelasticity and extend degradation time of the polymer Patela et al (). PGA with PCL has a better hydrophilicity and mechanical properties suited for soft‐tissue engineering and biocompatibility Aghdam et al ().…”
Section: Introductionmentioning
confidence: 99%